Chicken bone hydroxyapatite enhances collagen density and osteoblast cell number during bone formation of post-extraction socket wound healing process (an in vivo study) - Humani, Maria Bonita Cerebrina; Kintani, Dayinta Sekar; Arindra, Pingky Krisna; Karina, Vincensia Maria; Haniastuti, Tetiana (Majalah Kedokteran Gigi Indonesia, 2025)
Tooth extraction is a common dental procedure. Osteoblasts (bone-forming cells) and collagen are key indicators of wound healing following tooth extraction. Hydroxyapatite is a calcium-rich material that promotes the secretion of Fibroblast Growth Factor (FGF), Platelet-Derived Growth Factor (PDGF), and Transforming Growth Factor Beta (TGF-β)—all of which play critical roles in the wound healing process. Chicken bones, a natural source of hydroxyapatite, contain approximately 85% calcium phosphate minerals. This study aimed to determine the effect of chicken bone-derived hydroxyapatite on osteoblast cell count and collagen density in post-tooth extraction wounds in Wistar rats. Thirty male Wistar rats were randomly divided into treatment and control groups. Tooth extraction was performed on the lower left incisor of each rat. Hydroxyapatite was prepared by calcining chicken bones at 700 °C to remove organic material. The resulting hydroxyapatite powder was implanted into the tooth sockets of rats in the treatment group, while the control group received no implantation. Both groups were sutured and treated with povidone-iodine. Three rats from each group were sacrificed on days 3, 5, 7, 10, 14, and 21. Histological samples were prepared using hematoxylin-eosin and Mallory’s Trichrome staining. Osteoblast cells (100× magnification) and collagen density (400× magnification) were examined using a light microscope and Optilab Viewer, across five fields of view per sample. Two-way ANOVA showed significant differences in both osteoblast cell counts and collagen density between groups and across observation days (p < 0.05). Least Significant Difference (LSD) post hoc analysis also revealed significant differences between groups on all observation days (p < 0.05). In conclusion, chicken bone-derived hydroxyapatite significantly increases osteoblast numbers and collagen density during the post-extraction wound healing process in Wistar rats.